Stones into schools [large type] : promoting peace with books, not bombs, in Afghanistan and Pakistan - Mortenson, Greg (Thorndike Press, 2009)
In this dramatic first-person narrative, Greg Mortenson picks up where "Three Cups of Tea" left off in 2003, recounting his relentless, ongoing efforts to establish schools for girls in Afghanistan; his extensive work in Azad Kashmir and Pakistan after a massive earthquake hit the region in 2005; and the unique ways he has built relationships with Islamic clerics, militia commanders, and tribal leaders even as he was dodging shootouts with feuding Afghan warlords and surviving an eight-day armed abduction by the Taliban.